SOCIETAL SUSTAINABILITY VIA FINTECH ADOPTION: EXAMINING THE MEDIATING ROLE OF FINANCIAL INCLUSION UNDER PERCEIVED BENEFITS AND RISKS - Isadora Elgina Pramana; Adi Kurniawan Yusup (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
While FinTech is rapidly reshaping Indonesia’s financial landscape, there remains limited understanding of how young users, particularly Gen Z and Millennials, evaluate the trade-offs between perceived benefits and risks within this context. Addressing this gap, this study examines FinTech users in Surabaya (n = 142 valid responses) using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal a clear behavioral pathway in which monetary and non-monetary benefits do not directly influence FinTech adoption. Instead, these benefits significantly enhance Financial Inclusion, which functions as a critical prerequisite for adoption. Risk perceptions operate at different stages of the process. Security concerns significantly reduce perceived Financial Inclusion, while regulatory ambiguity directly weakens FinTech adoption. In contrast, financial risk shows no significant behavioral effect. The results further indicate that FinTech adoption does not significantly contribute to societal sustainability, suggesting that broader social outcomes depend more on structural and institutional enablers than on individual uptake alone. Overall, this study clarifies the central mediating role of Financial Inclusion and underscores the importance of secure user experiences and clear regulatory frameworks in translating digital participation into sustainable societal impact.